IKONISITAS BUNYI SUKU KATA ZHI DALAM BAHASA CINA - Budi Santoso (LITE: Jurnal Bahasa, Sastra, dan Budaya, 2009)
Iconicity of sound means a relationship between sound and meaning. The relationship results in index or icon. This study discusses the sound iconicity of zhi syllable in Chinese. The data were taken from Kamus Besar Tionghoa-Indonesia published in 1995. The result shows that the sound iconicity of zhi syllable is formed by 16 semantic categories in which diminutive semantics is dominant. The fair distribution of symbolic words in every semantics category shows that there is no element of syllable that distinguishes the diminutivesemantics category as the largest category. In addition, there are three factors that cause iconicity of sound, namely sound imitation, word etymology, and minimal amount of syllable.Key words: Chinese, Iconicity of sound, Icon, Index, Zhi syllable